Representing WWW navigational data: a graphical methodology to support qualitative analysis - Honey Lucas (Information Research: An International Electronic Journal)
This paper concerns the development and use of a graphical methodology in the analysis of individuals World Wide Web navigational behaviour. Specifically, it reports on the comparison of this methodology to other methodologies of qualitative analysis. Examples are given of the graphical representations of individuals interactions with particular World Wide Web medical resources, and the integration of these graphical representations with textual data considered. Indications for further development in this area are also suggested.